2005
DOI: 10.1063/1.1849836
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the threading dislocation density in GaN films grown on vicinal sapphire (0001) substrates

Abstract: Structural properties of GaN films grown on vicinal sapphire (0001) substrates with various vicinal angles by plasma-assisted molecular beam epitaxy are investigated. High-resolution x-ray diffraction (HRXRD) results reveal the dramatic improvement of both tilting and twisting grain features of the GaN films when the vicinal angle is larger than 0.5° with the formation of multilayer macro-steps on the surface. The threading dislocation density reduces by over an order of magnitude estimated from the HRXRD resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
90
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 16 publications
6
90
1
1
Order By: Relevance
“…www.pss-c.com [9], are clearly observable from the TEM image. The interesting feature is that the ITDs always terminate at macro-step positions on the surface as shown by arrows in the upper part of Fig.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…www.pss-c.com [9], are clearly observable from the TEM image. The interesting feature is that the ITDs always terminate at macro-step positions on the surface as shown by arrows in the upper part of Fig.…”
mentioning
confidence: 87%
“…Furthermore, the processes of the present techniques are very complicated, such as additional patterning, re-growth and etc. We have proposed a new approach to uniformly reduce the dislocation density [9]. This technique is simply to use vicinal substrates for the epitaxial growth without any additional processes.…”
mentioning
confidence: 99%
“…18 The growth of nitride films was performed with pulsed magnetron sputtering sources in an N 2 /Ar atmosphere. The growth temperature was monitored using a calibrated pyrometer.…”
mentioning
confidence: 99%
“…Our previous results clearly demonstrated that the surface morphology of the AlGaN/GaN heterostructure is free of micro-cracks by using vicinal substrate even the Al composition is as high as 0.4. Furthermore, the usage of the vicinal substrate can also reduce the dislocation density [8][9][10]. Therefore, it is expected that the gate leakage current in the HEMT can be suppressed by fabricating the device on the vicinal substrate.…”
Section: Resultsmentioning
confidence: 99%